IMPACT OF DIGITALISATION ON INDIAN ECONOMY (International Journal of Food and Nutritional Sciences, 2021)
India is fastest growing Economy in the world. The India economy is the seventh biggest economy of the world in terms of GDP and third biggest by purchasing power parity after USA and China. The Indian economy has seen a great deal of changes from acting self defendant to opening its entry way for worldwide exchanging by introducing LPG in 1991 under the leadership of finance Minister Dr. Manmohan Singh. Digitalization is a process to make people more advance in different field like banking, shopping, marketing, ticketing, etc to access easily in few seconds . Now our country moved towards a global hub of technology it require more advance movement in different field so do more work in less time . Due to digitalization process we do different work like bank work tax filling, electric bill payment ticket booking etc systematically in one time and in one place without hesitation. Digital India programme is a big step taken by the government of India to make this country a digitally empowered country, and aims to make India a better-governed place of the world Digital India, a much ambitious programme, It is very effective and efficient technique which will save time and man power to a great extent. The digital India programme is to connect people of rural areas with the high-speed internet networks to access any information needed. The aim of launching this campaign is to provide Indian citizens electronic government services by reducing the paperwork. Three important elements of digital India are like creation of digital infrastructure, digital literacy and delivering services digitally all over the country. This initiative was started on 1st of July in 2015 the Indira Gandhi Indoor Stadium, Delhi. This project has been approved (worth Rs 1 lakh crore) by the prime minister of India, Narendra Modi .It is the programme which will benefits both, service providers and consumers.